Pengaruh Penerapan Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Generik Sains Siswa Pada Materi Larutan Penyangga - Ratu Evina Dibyantini; Widya Azaria (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study was conducted to determine the effect of the forward model of Problem Based Learning on the generic ability of science students subject to buffer solutions. This research was conducted in class XI MIA Negeri 3 Medan in the academic year 2018/2019. The sample in this study consisted of two classes taken by random sampling, namely the experimental class with Problem Based Learning models and the control class with Direct Interaction models. Data collection techniques with the test method, in the form of questions about the subject of a buffer solution to measure the results of learning chemistry and the generic ability of science students (multiple choice). Data analysis using t test with independent sample t-test technique using SPSS version 20. Based on data analysis, the average value of student learning outcomes using problem based learning models increased from 34.02 to 80 compared to DI models from 31.94 to 74.58. This is supported by the results of hypothesis testing, obtained data that sig (2-tailed) <α or 0.003 <0.05, so that Ha is accepted and Ho is rejected. The data shows that the use of problem based learning models can affect the generic abilities of students' science.Keywords:Generic science skills, Problem based learning